Implementasi Pendekatan Kolaboratif melalui Model Project-Based Learning (PjBL) dalam Menanamkan Karakter Sosial Siswa SD - Agung Setyawan; Devi Amalia Fajri; Fatihatur Rahmaniyah; Badruddin (PT. Hasba Edukasi Mandiri, 2025)
This classroom action research investigates the implementation of a collaborative Project-Based Learning (PjBL) model to enhance the social character of fourth-grade students at SDN Banyuajuh 5, Bangkalan. The study involved 25 students and employed a project titled